New Hypoglycemic Drugs: Combination Drugs and Targets Discovery - Ni, Xiayun; Zhang, Lei; Feng, Xiaojun; Tang, Liqin (Frontiers in Pharmacology, 2022)
New hypoglycemic drugs, including glucagon-like peptide 1 receptor agonists (GLP-1RA), dipeptidyl peptidase-4 inhibitors (DPP-4i) and sodium-glucose cotransporter 2 inhibitors (SGLT-2i), which brings more options for the treatment of type 2 diabetes (T2DM). They are generally well tolerated, although caution is required in rare cases. Clinical trials have show good glycemic control with combination therapy with new hypoglycemic drugs in prediabetes and T2DM (mostly traditional stepwise therapy), but early combination therapy appears to have faster, more, and longer-lasting benefits. With the widespread clinical application of oral semaglutide, it is time to develop combinations drugs containing new hypoglycemic drugs, especially SGLT-2i and/or GLP-1RA, to control the risk of prediabetes and newly diagnosed T2DM and its cardiovascular complications, while improving patient compliance. Clinical and preclinical studies support that SGLT-2i exerts its protective effect on heart failure through indirect and direct effects. How this comprehensive protective effect regulates the dynamic changes of heart genes needs further study. We provide ideas for the development of heart failure drugs from the perspective of "clinical drug-mechanism-intensive disease treatment". This will help to accelerate the development of heart failure drugs, and to some extent guide the use of heart failure drugs.